Assessing Nursing Clinical Skills Performance Using Objective Structured Clinical Examination (OSCE) for Open Distance Learning Students in Open University Malaysia - Che'an Ahmad; Rosnida Abu Bakar; Nora Ahmad (2009)
Objective: The study assessed clinical competence level among distance learning nursing students’, using an objective structured clinical examination (OSCE). Study design: The cross sectional study method was used in this study. There are 5 stations of Objective Structured Clinical Examination. The researchers analyzed the level of competency from overall scores distribution using checklists. Results: The findings revealed that 43(14%) of the nurses have level four competencies, which indicates that they could perform the tasks correctly and complete. However, 36(12%) failed the OSCE, even though these nurses had more than ten years experience and post basic qualification. Among them were clinical instructors and nurse managers that give serious implications for nursing institution and services. The findings show that race, designation, current specialization and OSCE centers have an association with level of competency. Conclusion: An Objective Structured Clinical Exam is a necessary test that needs to be done continuously for tertiary nursing education programs, years of experiences and placement. This study supports the need for objective structured clinical examination in both the design of nursing degree programs and the assessment of nurses’ clinical competence level. (Author's abstract)